Blood flow responses over sacrum in nursing home residents during one hour bed rest. (October 2016) - Källman, Ulrika; Bergstrand, Sara; Ek, Anna‐Christina; Engström, Maria; Lindgren, Margareta
Abstract: Objectives: To describe individual BF responses in a nursing home resident population for one‐hour periods of bed rest. Methods: BF was measured for one hour over the sacrum in 0° supine position and 30° supine tilt position in 25 individuals aged 65 y or older while lying on a pressure‐redistributing mattress. Measurements were made at three tissue depths (1, 2, and 10 mm) using the noninvasive optical techniques, LDF and PPG. Results: Eleven participants had a PIV response at 1 mm depth in both positions and seven participants had a lack of this response at this depth and positions. The BF response at 1 mm depth appeared immediately and remained over, or below, baseline for the entire 60 min of loading in both positions. These BF patterns were also seen in deeper tissue layers. Conclusions: The cutaneous BF response among the nursing home residents was distinct, appeared early, and remained during the one hour of loading.